Endovascular revascularization of multilevel arterial disease in patients with critical limb ischemia - Goda, Asser Abd El Hamid (International Surgery Journal, 2018)
Background: Critical limb ischemia (CLI) occurs due to progressive obstructive nature of atherosclerosis disease. Nowadays, there is widespread use of endovascular revascularization procedures for restoration of blood flow in CLI. The aim this study is evaluation of the efficacy of endovascular intervention for multilevel arterial disease in patients with critical limb ischemia. Methods: This prospective study was included CLI patients due to multilevel arterial disease who underwent endovascular revascularization between January 2016 and January 2017 in our institution. Study end points were limb salvage and wound healing. Results: The mean age of patients was (61.7±7.47) years, with 13 (61.9%) men. Eight limbs were identified as Rutherford category 4 (38.1%), ten limbs as Rutherford category 5 (47.6%), and three limbs as Rutherford category 6 (14.3%). Limb salvage rate was (90.5%) at 1 year. Wound healing rate was 80.9%. Conclusions: This study proved that endovascular revascularization of multilevel arterial disease for patients with critical limb ischemia is effective.